Effectiveness of social media-based health promotion campaign in reducing smoking behavior among adolescents - Fadli, Khalikul; Tawil, Muhammad Risal; Pannyiwi, Rahmat; Nuryani, Siti; Dewi, Chitra (Institute Of Computer Science (IOCS), 2025)
Adolescent smoking remains a significant health problem in many countries, including Indonesia. One approach that is considered effective in addressing this problem is a social media-based health promotion campaign, which is able to reach adolescents widely and intensively. This study aims to analyze the impact of social media-based health promotion campaigns on reducing adolescent smoking behavior. The method used was mixed quantitative and qualitative, involving descriptive and inferential statistical analysis of 150 adolescent respondents as well as in-depth interviews to explore their perspectives. The results showed that there was a significant decrease in smoking frequency after exposure to the campaign (p < 0.05), and respondents reported that the engaging and relevant content of the campaign influenced their decision to reduce or quit smoking. The implications of this study suggest that social media-based campaigns can be an effective strategy in changing adolescents' health behaviors, especially related to smoking control, and can be more widely adopted in public health policy.